Weird : the Al Yankovic story [compact disc]. - Birenberg, Leo; Robinson, Zach; Light, Dan; Rodriguez, Ramiro (SMG, 2023)
A mix of newly recorded classic Weird Al parodies, a new Weird Al original (Now You Know), various other artists' tracks, and the film's orchestral score by Leo Birenberg and Zach Robinson (the team behind the score for the Netflix blockbuster Cobra Kai) on a jam-packed single CD.